Festival of colors - Sehgal, Kabir; Sehgal, Surishtha (Beach Lane Books, 2018)
Sibilings Chintoo and Mintoo collect flowers and press the petals into a fine powder as they prepare for Holi, the Indian springtime Festival of Colors. Includes author's note
Keywords: JUVENILE FICTION / People & Places / Asia / bisacsh; JUVENILE FICTION / Holidays & Celebrations / Other, Religious / bisacsh; JUVENILE FICTION / Family / Siblings / bisacsh; Holī (Hindu festival); Color; Flowers; JUVENILE FICTION / People & Places / Asia; JUVENILE FICTION / Holidays & Celebrations / Other, Religious; JUVENILE FICTION / Family / Siblings; Bilderbuch; Kinderbuch